Application of Other than Accrual and Matching Generally Accepted Accounting Principles for the Purpose of Legal Entities Taxation on Corporate Income Tax - Endrijaitis, Martynas (Teisė, 2018)
The article discloses de facto application of other than accrual and matching generally accepted accounting principles for the purpose of legal entities taxation on corporate income tax. Research reveals designation which generally accepted accounting principles could be described as “dormant” in taxation simultaneously disclosing which principles have their own fiscal meaning.
Keywords: none